Posterior mediastinal benign cystic teratoma in an infant – a rare cause of recurrent respiratory distress - Beura, Subhasree; Mishra, Baikuntha Narayan; Joshi, Ranjit Kumar; Pahi, Prabin Prakash; Sadhukhan, Meghmala (Indian Journal of Child Health, 2020)
Mediastinal benign teratoma is a rare primary germ cell neoplasm composed of well-differentiated tissues derived from more than one of the three embryonic germ cell layers. Most of the mediastinal teratomas are found in the anterior mediastinum. The posterior mediastinal teratomas are rare. We describe a rare case of an infant with benign cystic teratoma in the posterior mediastinum presenting with recurrent respiratory distress, successfully treated by surgical excision with no recurrence in a 1-year follow-up.